Free fatty acids may regulate the expression of 11β-hydroxysteroid dehydrogenase type 1 in the liver of high-fat diet golden hamsters through the ERS-CHOP-C/EBPα signaling pathway - Dandan Liu; Peipei Tian; Yilin Hou; Tingxue Zhang; Xiaoyu Hou; Lifang Liu; Xiaolong Li; Kunjie Zheng; Chao Wang; Guangyao Song (Lipids in Health and Disease)
Abstract Objective Free fatty acids (FFA) can increase the expression of 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1) in local tissues and organs. However, the mechanism underlying the effect of FFA on 11β-HSD1 expression remains unclear. Methods A total of 24 male Syrian golden hamsters (SPF grade) were selected and randomly divided into a control group (Con, n = 8) fed a normal diet, and a high-fat diet group (n = 16) fed for 12 weeks. After successfully establishing the hyperlipidemia hamster model, the high-fat group was further divided into a high-fat group (HF) and a fenofibrate intervention group (Feno). Following an oral fat tolerance test (OFTT), blood lipids and FFA levels were measured. The expression levels of endoplasmic reticulum stress (ERS) marker GRP78, downstream key molecule CHOP, C/EBPα, and 11β-HSD1 were analyzed using Western blot and RT-PCR. Results After OFTT, FFA levels in all three groups initially decreased and then increased, with the highest levels observed in the HF group (Ps < 0.05). FFA levels in the Feno group were comparable to those in the Con group (P > 0.05). Hepatic FFA, 11β-HSD1, and corticosterone levels were highest in the HF group (Ps < 0.05), while the Feno group showed no significant difference compared to the Con group (Ps > 0.05). Hepatic 11β-HSD1 and corticosterone levels were positively correlated with FFA levels (Ps < 0.05). Western blot and RT-PCR results indicated higher GRP78, CHOP, C/EBPα, and 11β-HSD1 protein and mRNA expression in the HF group compared to the Con group (Ps < 0.05). Fenofibrate intervention reduced FFA levels and downregulated these indicators in the Feno group compared to the HF group (Ps < 0.05). Conclusion FFA may regulate the expression of hepatic 11β-HSD1 in high-fat-fed golden hamsters via the ERS-CHOP-C/EBPα signaling pathway, thereby affecting local corticosterone levels. Fenofibrate may downregulate the levels of 11β-HSD1 and corticosterone in local tissues by reducing FFA levels.